Gender gap in the CIS region - Magdalena Rokicka (Center for Social and Economic Research (CASE), 2008)
The aim of this paper is to examine the issues of gender disparities in the Commonwealth of Independent States (CIS) region, with a special focus given to countries covered by the European Neighbourhood Policy (ENP)1. The analysis is conducted in several dimensions: labour participation, economic opportunity, political empowerment, educational attainment, and health and demography2. Beside the comparative study of in region differentials” done for the CIS, I analyze the trends in gender disparities in comparison to: EU-12 and EU-15, using data for the period 1985-2005. The study confirms the existence of slightly different paths in which gender disparities have evolved over time. While in EU-15 women participation in labour market, their remuneration, and position in public life have significantly increased, in majority of the CIS countries a gradual decrease of female labour activity was reported. In addition female representation in politics and public life has shrunken after and during the transition period. On the other hand in such fields as secondary and tertiary education attainment, health, and demography male population in the CIS region has became more disadvantaged, which also leads to enlarging gender gap.
Keywords: J16; J24; J21; J70; 330; gender gap; employment; education; transition economies; Gleichberechtigung; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Lohnstruktur; Erwerbstätigkeit; Partizipation; Bildungsabschluss; Gesundheit; GUS-Staaten